2013
DOI: 10.1063/1.4807514
|View full text |Cite
|
Sign up to set email alerts
|

LUNASKA neutrino search with the Parkes and ATCA telescopes

Abstract: The Moon is used as a target volume for ultra-high energy neutrino searches with terrestrial radio telescopes. The LUNASKA project has conducted observations with the Parkes and ATCA telescopes; and, most recently, with both of them in combination. We present an analysis of the data obtained from these searches, including validation and calibration results for the Parkes-ATCA experiment, as well as a summary of prospects for future observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…At EeV energies, relevant for the detection of cosmogenic neutrinos produced in the interactions of cosmic rays with background microwave photons, this is no longer the case and saturation effects must be included in evaluating the sensitivity of ARA [24], ANITA [25], ARIANNA [26], JEM-EUSO [27], and LUNASKA [28]. Our formalism provides a prediction of the EeV-neutrino cross section that, although relying on a (dipole) parameterization, is directly supported by a wealth of data.…”
Section: Introductionmentioning
confidence: 99%
“…At EeV energies, relevant for the detection of cosmogenic neutrinos produced in the interactions of cosmic rays with background microwave photons, this is no longer the case and saturation effects must be included in evaluating the sensitivity of ARA [24], ANITA [25], ARIANNA [26], JEM-EUSO [27], and LUNASKA [28]. Our formalism provides a prediction of the EeV-neutrino cross section that, although relying on a (dipole) parameterization, is directly supported by a wealth of data.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our 120-hour observations using the Kalyazin 64-m radio telescope (Russia) in the 1.4 GHz and 2.3 GHz frequency ranges [24] showed that the rate of the radio pulses resulting in interactions of neutrinos with energy above 10 20 eV with atoms of the lunar regolith does not exceed (200 hrs) −1 or 1.4 10 −6 sec −1 . In subsequent years many more attempts were undertaken to register the bursts of Cherenkov radio emission from the Moon using the Westerbork synthesis radio telescopes (The Netherlands), some part of the VLA antennae (USA), again the Parks 64-m radio telescope, and other radio astronomy tools [25][26][27][28][29]. The new essentially stronger upper limit to the EHE neutrino flux was obtained from these experiments.…”
Section: Ramhand: the Past And The Prospectsmentioning
confidence: 99%
“…In particular, Singh et al [40] have proposed lunar radio observations with LOFAR, an aperture array telescope currently in its commissioning phase, and Bray et al [41] have proposed continued use of the Parkes radio telescope used in this experiment, using one of the Phased Array Feed (PAF) receivers recently developed for ASKAP [42]. Both of these proposed experiments would utilise multiple beams pointing on the Moon with a real-time anticoincidence filtering scheme to identify lunarorigin Askaryan pulses.…”
Section: Considerations For Future Experimentsmentioning
confidence: 99%